Mesothelioma rates in South Africa: trends 1995–2008. (19th October 2011) - Nattey, Cornelius; Kielkowski, Danuta; Bello, Briamoh; Nelson, Gill; Fadahun, Jimi; Phillips, Jill
Abstract : Objectives: Mesothelioma is a rare neoplasm which is caused by asbestos exposure. South Africa has mined and refined all three types of asbestos since 19th century with the peak of production in1940–1980s. At present asbestos use and production is banned in South Africa. Trend 1995–2008 in mesothelioma rate was assessed to determine burden of asbestos related deaths due to mesothelioma by year and gender. Methods: Death certificates with underlying cause of death stated as C45 were selected for the study in 1995–2008. For each year of study, age and gender distribution was obtained from the national statistical releases. Mesothelioma rates, 95% CI were calculated for each year and sex, and for age groups and sex. Poisson regression model was used to test for trends. Results: In total 2497 cases were identified of deaths due to mesothelioma, 1919 in men and 578 in women in the study period. There was 3:1 male to female ratio. The trend was stable and constant over time for both men and women cases. Mortality in men was 8-16 per million and in women 2–5 per million. Conclusions: If mortality remains at current estimates, we can expect 2134 cases by 2020. However, it is authors opinion that mortality is underestimated due to the competing causes of death, and shortened longevity. Just looking at other countries and their diagnosed cases, such as Great Britain, major consumer of asbestos from South Africa, it becomes apparent how little mesothelioma cases are diagnosed in our country.